Sound insulation performance of different built-in acoustic materials for new multifamily residential - Wenchin Chung; Mingyeh Hsieh (Journal of Asian Architecture and Building Engineering)
The Building Technical Regulations in Taiwan, Article 46–6, Section 1. require that the impact sound insulation performance △LW be greater than 17 dB. Although the regulation has been in effect for over 2.5 years, installations of qualified acoustic materials have not yet been found in the market, as they are not required to be listed for building permit applications until 2021. Owing to the slow increase in new home construction, sound insulation mats are estimated to take five to seven years to be widely adopted. To characterize the material performance, the built-in permanent sound insulation layers of various materials were tested in an unfinished residential building. Practical experiments were conducted as per the CNS 15160-7:2021standard on the 7th floor of new buildings in northern Taiwan. Eleven insulation materials were selected from different manufacturers. The insulation mats made from these materials were placed in the same environment of approximately 10 M2, then incorporated underneath the mortar substrate of the polished floor tile using the wet construction method; the 6th floor of the building was utilized to evaluate sound reduction in accordance with the CNS 8465–2:2019 standard for different materials.